A novel carboxylic-functional indole-based aerogel for highly effective removal of heavy metals from aqueous solution via synergistic effects of face–point and point–point interactions. Issue 43 (12th August 2019) - Yang, Li; Yang, Peng; Ma, Yuanchi; Chang, Guanjun
Abstract : A new type of carboxylic-functional indole-based aerogel (CHIFA) has been successfully prepared, which possessed highly effective removal of heavy metals from aqueous solution through the synergistic effects of face–point and point–point interactions. Abstract : A new type of carboxylic-functional indole-based aerogel (CHIFA) has been successfully prepared via a facile sol–gel technology, which possessed a highly effective removal of heavy metals from aqueous solution through the synergistic effects of face–point and point–point interactions.